Lifetime cannabis use and childhood trauma increase risk of psychosis in carriers of CNR1 genetic variants: findings from the STREAM study - Camila Marcelino Loureiro; Fabiana Corsi-Zuelli; Helene Aparecida Fachim; Rosana Shuhama; Adrielle Martins de Oliveira; Paulo Rossi Menezes; Caroline F. Dalton; Paulo Louzada-Junior; Sintia Iole Belangero; Fernanda Coeli-Lacchini; Gavin P. Reynolds; Riccardo Lacchini; et al. (Brazilian Journal of Psychiatry, 2023)
Objectives: Gene-environment interactions increase the risk of psychosis. The objective of this study was to investigate gene-gene and gene-environment interactions in psychosis, including single nucleotide variants (SNVs) of dopamine-2 receptor (D2R), N-methyl-d-aspartate receptor (NMDAR), and cannabinoid receptor type 1 (CB1R), lifetime cannabis use, and childhood trauma. Methods: Twenty-three SNVs of genes encoding D2R (DRD2: rs1799978, rs7131056, rs6275), NMDAR (GRIN1: rs4880213, rs11146020; GRIN2A: rs1420040, rs11866328; GRIN2B: rs890, rs2098469, rs7298664), and CB1R (CNR1: rs806380, rs806379, rs1049353, rs6454674, rs1535255, rs2023239, rs12720071, rs6928499, rs806374, rs7766029, rs806378, rs10485170, rs9450898) were genotyped in 143 first-episode psychosis patients (FEPp) and 286 community-based controls by Illumina HumanCoreExome-24 BeadChip. Gene-gene and gene-environment associations were assessed using nonparametric Multifactor Dimensionality Reduction software. Results: Single-locus analyses among the 23 SNVs for psychosis and gene-gene interactions were not significant (p > 0.05 for all comparisons); however, both environmental risk factors showed an association with psychosis (p < 0.001). Moreover, gene-environment interactions were significant for an SNV in CNR1 and cannabis use. The best-performing model was the combination of CNR1 rs12720071 and lifetime cannabis use (p < 0.001), suggesting an increased risk of psychosis. Conclusion: Our study supports the hypothesis of gene-environment interactions for psychosis involving T-allele carriers of CNR1 SNVs, childhood trauma, and cannabis use.